Binary metal catalyst material as well as preparation method and application thereof

By forming a Pt-X/Ti catalyst on the surface of a metal substrate, the scaling problem of the cathode electrode in neutral seawater electrolysis is solved by utilizing the coordination structure, thereby improving the stability and activity of the catalyst and making it suitable for large-scale production.

CN120925012APending Publication Date: 2025-11-11NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511064103.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

In existing technologies, the cathode electrode is prone to scaling during neutral seawater electrolysis, resulting in poor stability. Existing binary metal catalysts, such as Pt/Ti catalysts, have insufficient activity and stability in neutral seawater.

Method used

A modified metal layer is deposited on the surface of a first metal substrate using an in-situ synthesis coordination method to form a composite metal material. A second metal is then bonded to the coordinating atoms through coordination bonds to form a ligand structure, which is then deposited on the surface of the first metal substrate. Specific processes include electroplating or chemical plating, using metals such as titanium and platinum, with halogen atoms as the coordinating atoms, to form a Pt-X/Ti catalyst.

Benefits of technology

It improves the stability and activity of the catalyst, reduces the aggregation of hydroxide ions on the catalyst surface, alleviates or eliminates scaling, and reduces the voltage by 100mV when the current density reaches 100mA/cm-2. It is suitable for large-scale production and has low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120925012A_ABST
    Figure CN120925012A_ABST
Patent Text Reader

Abstract

The invention discloses a binary metal catalyst material containing a coordination structure as well as a preparation method and application of the binary metal catalyst material. The preparation method of the catalyst material comprises the following steps: depositing a modified metal layer on the surface of a first metal matrix by adopting an in-situ synthesis coordination method to form a composite metal material; wherein the modified metal layer comprises a second metal which is combined with a coordination atom through a coordination bond and is deposited on the surface of the first metal matrix. According to the technical scheme, the in-situ synthesis coordination method is adopted, and the second metal is replaced on the surface of the first metal matrix material, is combined with the halogen atom ligand and is deposited on the surface of the first metal matrix material instead of entering the first metal matrix, so that the activity of the catalyst can be effectively improved, and the service life of the catalyst is prolonged. The scaling phenomenon on the surface of the catalyst can be effectively inhibited, the stability of the catalyst is improved, the process is simple, the consumption of required coordination metal elements is small, the cost is low, and the catalyst is suitable for large-scale production and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrode material technology, specifically relating to a binary metal catalyst material with a coordination structure, its preparation method, and its application. Background Technology

[0002] With industrialization and a continuously increasing global population, human society is facing an increasingly severe energy crisis, and the demand for hydrogen energy is growing. Seawater is an inexhaustible electrolyte, but because it is neutral, the cathode electrode is prone to scaling, making it difficult to maintain long-term stability in seawater electrolysis. Developing a cathode electrode that remains stable during electrolysis in neutral seawater remains a significant challenge.

[0003] Platinum is one of the most widely used cathode catalysts for water electrolysis, characterized by good HER activity and stability. However, in long-term use in neutral seawater environments, platinum will become deactivated due to the deposition of calcium and magnesium ions. In-situ synthesis of Pt-X coordination bonds is usually required to improve the catalytic stability of platinum atom reactions. However, noble metal catalysts with Pt-Cl sites represented by halogen coordination of platinum atoms still have problems such as poor reaction stability.

[0004] Catalysts composed of simple binary metal materials, especially Pt / Ti catalysts, suffer from poor reactivity and stability. For example, Chinese invention patent CN118222953A discloses a method for improving the surface energy of nickel metal, a nickel-copper binary metal material and its application. It discloses an electroplating or chemical plating process to make the two metals a solid solution. A small amount of modified metal is deposited on the surface of the nickel metal substrate, and then a short heat treatment is performed to allow the modified metal atoms to diffuse on the surface of the nickel metal substrate and mix uniformly with nickel atoms, rather than entering the interior of the nickel metal substrate and forming an ordered alloy structure. This can effectively improve the atomic disorder on the surface of the nickel metal substrate. It has the advantages of simple process, small amount of modified metal required, and low cost. However, when applied to Pt / Ti catalysts, it still cannot solve the problems of poor activity and stability caused by scaling in neutral seawater. Summary of the Invention

[0005] The purpose of this invention is to provide a binary metal catalyst material with a coordination structure, its preparation method and application, so as to solve the problems of easy scaling and poor stability of the cathode in the prior art of seawater electrolysis.

[0006] To achieve the above-mentioned objectives, the present invention adopts the following technical solution.

[0007] As a first aspect of the invention, the present invention provides a method for preparing a binary metal catalyst material containing a coordination structure, comprising using an in-situ synthetic coordination method to deposit a modified metal layer on the surface of a first metal substrate to form a composite metal material; wherein the modified metal layer comprises a second metal and coordinating atoms bonded by coordination bonds to form a ligand structure, and deposited on the surface of the first metal substrate.

[0008] In some specific embodiments, the in-situ synthesis coordination method includes: immersing a first metal substrate in an electroplating or chemical plating solution using an electroplating or chemical plating process, and then depositing the second metal particles together with the coordinating atoms on the surface of the first metal substrate through coordination bonds.

[0009] In some specific embodiments, the first metal matrix includes any one of titanium matrix, nickel matrix, etc., but is not limited thereto.

[0010] In some specific embodiments, the purity of the first metal matrix is ​​≥99%.

[0011] In some specific embodiments, the second metal includes at least one of palladium, platinum, ruthenium, manganese, etc., but is not limited thereto.

[0012] In some specific embodiments, the second metal source includes at least one of the sulfate, nitrate, and chloride salts of the second metal, but is not limited thereto.

[0013] In some specific embodiments, the coordinating atom is a halogen atom.

[0014] In some specific embodiments, the titanium matrix includes at least one of titanium sheets, titanium mesh, titanium foam, etc., but is not limited thereto.

[0015] In some specific embodiments, the nickel substrate includes at least one of nickel sheet, nickel mesh, nickel foam, etc., but is not limited thereto.

[0016] In some specific embodiments, the electroplating solution or the chemical plating solution is a mixed solution comprising at least the second metal source solution, the coordination ion solution, and the potassium salt solution; the coordination ion solution provides coordination atoms, and the potassium salt solution can increase conductivity.

[0017] In some specific embodiments, the conditions of the electroplating process include: a temperature of 20 to 50°C, a voltage of -0.1 to -1.5V, a time of 5 to 30 minutes, and the concentration of the second metal source solution in the electroplating solution being 0.0015 to 0.015 mol / L and the concentration of the potassium salt solution being 0.05 to 0.2 mol / L.

[0018] In some specific embodiments, the conditions of the electroless plating process include: the electroless plating solution contains 0.01-1 mol / L of a second metal source, 0.01-1 mol / L of a complexing agent and 0.01-1 mol / L of a reducing agent, and the electroless plating time is 5-30 min.

[0019] In some specific embodiments, the potassium salt solution includes at least one of potassium nitrate, potassium sulfate, potassium acetate, etc., but is not limited thereto.

[0020] In some specific embodiments, the complexing agent includes at least one of sodium tartrate, sodium citrate, ethylenediaminetetraacetic acid, sodium pyrophosphate, etc., but is not limited thereto.

[0021] In some specific embodiments, the reducing agent includes at least one of sodium hypophosphite, sodium borohydride, borane, etc., but is not limited thereto.

[0022] In some specific embodiments, the first metal matrix material further includes pretreatment before deposition.

[0023] In some specific embodiments, the pretreatment includes: removing contaminants from the surface of the metal substrate using at least organic solvents and / or alkaline solutions.

[0024] In some specific embodiments, the pretreatment involves at least using an acidic reagent to remove the oxide layer on the surface of the metal substrate.

[0025] As a second objective of the invention, the present invention also provides a binary metal catalyst material containing a coordination structure, prepared by the in-situ chemical synthesis method described above.

[0026] In some specific embodiments, the content of the second metal atoms deposited on the surface of the first metal substrate is 70-75%; the content of ligand atoms is 25-30%.

[0027] In some specific embodiments, the second metal is platinum, the ligand atom is a halogen atom, and the first metal is titanium.

[0028] As a third objective of the invention, the present invention also provides a binary metal catalyst material as described above or its use in the electrolysis of neutral seawater to produce hydrogen.

[0029] As a fourth objective of the invention, the present invention also provides an electrode for producing hydrogen by electrolysis of neutral seawater, the electrode comprising the binary metal catalyst material as described above.

[0030] As a fifth objective of the invention, the present invention also provides a water electrolysis hydrogen production system, including a hydrogen evolution electrode and an oxygen evolution electrode, wherein at least one of the hydrogen evolution electrode and the oxygen evolution electrode comprises the binary metal catalyst material described above; or the electrode for hydrogen production by electrolysis of neutral seawater described above.

[0031] Compared with the prior art, the present invention has at least the following beneficial effects:

[0032] 1. The technical solution of this invention employs an in-situ synthesis and coordination method to co-deposit catalytic metal elements such as palladium, platinum, ruthenium, and manganese with halogen elements on the surface of a metal matrix such as a titanium mesh, without penetrating the interior of the metal matrix. This allows for uniform mixing of catalytic metal atoms and halogen atoms on the catalyst material surface. The negative charge carried by the halogen elements repels hydroxide ions generated during water electrolysis, reducing the accumulation of Mg(OH)₂ and other substances on the catalyst material surface, alleviating or eliminating scaling, and thus ensuring the activity and stability of the catalyst. Furthermore, the catalytic particles formed by this invention are spherical, with a significantly increased specific surface area compared to regularly shaped particles, further enhancing the stability and catalytic activity of the catalyst material. Additionally, when applied to water electrolysis for hydrogen evolution, the catalyst material of this invention achieves a current density of 100 mA / cm². -2 The voltage can be reduced by at least 100mV.

[0033] 2. The catalyst material of the present invention can be prepared by electroplating or chemical plating under normal temperature and pressure conditions. The process is simple, requires few precious metal elements, has low cost, is suitable for large-scale production, and has broad application prospects in fields such as water electrolysis and hydrogen evolution. Attached Figure Description

[0034] Figure 1 This is a magnified SEM image of a single platinum metal particle in the metal layer deposited on the surface of a titanium mesh in Embodiment 1 of the present invention.

[0035] Figures 2-5 The images shown are Raman spectra of the Pt-X / Ti catalyst provided in Example 1 of this invention.

[0036] Figure 6 This is a stability test diagram of the Pt-I / Ti catalyst provided in Example 1 of the present invention after hydrolysis in natural seawater for 1 hour.

[0037] Figure 7 The graph shows the relationship between the current density and electrode potential during the hydrolysis of the Pt-I / Ti catalyst provided in Example 1 of this invention in natural seawater.

[0038] Figure 8 This is a stability test diagram of the Pt-Br / Ti catalyst provided in Example 1 of the present invention after hydrolysis in natural seawater for 1 hour.

[0039] Figure 9 The graph shows the relationship between the current density and electrode potential during the hydrolysis of the Pt-Br / Ti catalyst provided in Example 1 of this invention in natural seawater.

[0040] Figure 10 This is a stability test diagram of the Pt-Cl / Ti catalyst provided in Example 1 of the present invention after hydrolysis in natural seawater for 1 hour.

[0041] Figure 11 The graph shows the relationship between the current density and electrode potential during the hydrolysis of the Pt-Cl / Ti catalyst provided in Example 1 of this invention in natural seawater.

[0042] Figure 12 This is a stability test diagram of the Pt-F / Ti catalyst provided in Example 1 of the present invention after hydrolysis in natural seawater for 1 hour.

[0043] Figure 13 The graph shows the relationship between the current density and electrode potential during the hydrolysis of the Pt-F / Ti catalyst provided in Example 1 of this invention in natural seawater.

[0044] Figure 14 This is a stability test diagram of the Pt / Ti catalyst of Comparative Example 1 of the present invention after hydrolysis in natural seawater for 1 hour.

[0045] Figure 15 The current density and electrode potential of the Pt / Ti catalyst provided in Comparative Example 1 of this invention during hydrolysis in natural seawater are shown.

[0046] Figures 16-19 The images show the EDS elemental distribution of the Pt-X / Ti catalyst provided in Example 1 of this invention.

[0047] Figures 20-23 The figures are Pt-X coordination distribution diagrams in the Pt-X / Ti (X = F, Cl, Br, I) catalyst provided in Example 1 of this invention.

[0048] Figure 24 This is an SEM image of platinum metal particles in the metal layer deposited on the surface of a titanium mesh in Example 1.

[0049] Figure 25 The current density and electrode potential of the Pt-F / Ti catalyst provided in Example 21 of this invention during hydrolysis in natural seawater are shown.

[0050] Figure 26 This is a stability test diagram of the Pt-F / Ti catalyst provided in Example 21 of the present invention in natural seawater for 1 hour of catalytic reaction. Detailed Implementation

[0051] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments.

[0052] Some embodiments of this application provide a method for in-situ chemical synthesis of binary metal catalysts, including using an in-situ coordination synthesis method to deposit a modified metal layer on the surface of a first metal substrate to form a composite metal material; wherein, the modified metal layer comprises a second metal and its coordinating atoms uniformly mixed and co-deposited on the surface of the first metal substrate.

[0053] The first metal matrix is ​​a titanium matrix or a nickel matrix with a purity higher than 99%.

[0054] Furthermore, the titanium matrix includes, but is not limited to, at least one of titanium sheets, titanium mesh, and titanium foam.

[0055] Alternatively, the nickel matrix may include, but is not limited to, at least one of nickel sheets, nickel mesh, and nickel foam.

[0056] The second metal includes, but is not limited to, at least one of palladium, platinum, ruthenium, and manganese.

[0057] In some embodiments, the selection of a first metal matrix as a titanium mesh, a second metal as platinum, and coordinating atoms as halogen atoms are described in detail.

[0058] Specifically, the catalyst material prepared was Pt-X / Ti.

[0059] Preferably, a mixed electroplating solution containing chloroplatinic acid, NaX, and potassium salt is prepared, and the pretreated titanium mesh is electroplated in the mixed electroplating solution to obtain the corresponding Pt-X / Ti catalyst.

[0060] The content of coordinating atoms on the surface of the electrode material is preferably 20-25%, more preferably 20-22%.

[0061] In one embodiment, the method for preparing the Pt-X / Ti electrode specifically includes: depositing a modified metal layer on the surface of a pretreated metal substrate using at least an electroplating or electroless plating process to form a composite metal material.

[0062] In one embodiment, the electroplating process conditions include: a temperature of 20–50°C, a voltage of -0.1–-1.5V, a time of 5–30 min, a metal source concentration of 0.0015–0.015 mol / L in the electroplating solution, and a salt solution concentration of 0.05–0.2 mol / L.

[0063] Preferably, the electroplating process conditions include: a temperature of 20–40°C, a voltage of -0.3–-0.5V, a time of 10–20 min, a metal source concentration in the electroplating solution of 0.0015–0.005 mol / L, and a salt solution concentration of 0.1–10.2 mol / L. Using these process conditions can obtain a metal coating of suitable thickness and avoid the formation of ordered structures.

[0064] In one embodiment, the conditions of the electroless plating process include: the electroless plating solution contains 0.01–1 mol / L of metal source, 0.01–1 mol / L of complexing agent and 0.01–1 mol / L of reducing agent, and the electroless plating time is 5–30 min.

[0065] Preferably, the electroless plating process includes the following conditions: the electroless plating solution contains 0.1–1 mol / L of metal source, 0.1–1 mol / L of complexing agent, and 0.1–1 mol / L of reducing agent, and the electroless plating time is 5–15 min. Using these process conditions, a metal coating of suitable thickness can be obtained.

[0066] In one embodiment, the metal source includes at least one of sulfates, nitrates, chlorides, etc., containing a second metal element, and is not limited thereto.

[0067] In one embodiment, the salt solution includes at least one of potassium nitrate, potassium sulfate, potassium acetate, etc., but is not limited thereto.

[0068] More preferably, in the electroplating process, the metal source is a chloride salt containing a second metal element, and the salt solution is potassium nitrate, so as to obtain a more uniform metal coating.

[0069] Preferably, in the chemical plating process, the metal source is a metal chloride salt containing a second metal element, and the salt solution is potassium nitrate, so as to obtain a more uniform metal coating.

[0070] In one embodiment, the pretreatment includes: removing contaminants from the surface of the metal substrate using at least an organic solvent and / or an alkaline solution; and removing the oxide layer from the surface of the metal substrate using at least an acidic reagent. The contaminants are primarily oil stains.

[0071] In one embodiment, the alkaline solution includes at least one of sodium hydroxide and potassium hydroxide, but is not limited thereto.

[0072] In some cases, the concentration of the alkaline solution is 0.5 mol / L to 5 mol / L.

[0073] In some cases, the acidic reagent includes either sulfuric acid or hydrochloric acid, with a concentration of 0.5 mol / L to 5 mol / L.

[0074] In one embodiment, the organic solvent includes at least one of anhydrous ethanol and anhydrous acetone, but is not limited thereto.

[0075] Some embodiments of this application provide a Pt-X / Ti cathode electrode material prepared by the in-situ electrochemical synthesis method described above.

[0076] Some embodiments of this application provide a Pt-X / Ti cathode electrode material with a surface having a uniform mixture of platinum metal atoms and coordinating atoms, and the platinum metal atom content on the surface of the metal material is 70-75%.

[0077] In some specific embodiments, the modified metal includes, but is not limited to, at least one of palladium, platinum, ruthenium, and manganese.

[0078] In one embodiment, the Pt-X / Ti cathode electrode material comprises 70-75% platinum metal atoms and 25-30% coordinating atoms.

[0079] Some embodiments of this application provide Pt-X / Ti cathode electrode materials in which copper atoms and coordinating atoms are uniformly mixed on the surface of the metal material, and the copper atom content on the surface of the metal material is 70-75%.

[0080] In one embodiment, the Pt-X / Ti cathode electrode material comprises 70-75% platinum atoms and 25-30% coordination atoms.

[0081] Some embodiments of this application provide the use of the Pt-X / Ti cathode electrode material in the field of water electrolysis, such as in water electrolysis for hydrogen production.

[0082] Some embodiments of this application provide an electrode for producing hydrogen by water electrolysis, which comprises the Pt-X / Ti cathode electrode material.

[0083] Some embodiments of this application provide a water electrolysis hydrogen production system, including a hydrogen evolution electrode and an oxygen evolution electrode, wherein at least one of the hydrogen evolution electrode and the oxygen evolution electrode comprises a binary metal material.

[0084] The technical solution of the present invention will be explained in more detail below with reference to several embodiments.

[0085] Example 1

[0086] This embodiment provides a method for preparing a Pt-X / Ti catalyst, including the following steps:

[0087] 1. Prepare the electroplating solution

[0088] The electroplating solution consists of 0.0003 mol chloroplatinic acid, 0.2 mol NaX, and 0.02 mol potassium nitrate dissolved in 200 mL of deionized water, wherein NaX represents NaF / NaCl / NaBr / NaI, respectively.

[0089] 2. Pre-treatment of titanium mesh

[0090] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0091] 3. Electroplating deposition of Pt-X metal layer.

[0092] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 20 minutes at a voltage of -0.3V and a stirring speed of 300r to obtain the corresponding Pt-X / Ti catalyst.

[0093] See Figure 24 SEM of catalyst surface Figure 1 for Figure 24 The magnified image of a single metal particle shows that the particle is composed of Pt atoms.

[0094] See Figures 2-5 The figures show the Raman spectra of Pt-F, Pt-Cl, Pt-Br, and Pt-I, respectively. As can be seen from the figures, the deposited metal layer contains a Pt-X structure, indicating that the prepared catalyst is Pt-X / Ti.

[0095] See Figures 16-19 The following are the EDS elemental distribution diagrams of the Pt-X / Ti catalyst provided in this embodiment; see below. Figures 20-23 Tables 1-4 show the coordination distribution of Pt-X in Pt-I / Ti, Pt-Br / Ti, Pt-Cl / Ti, and Pt-F / Ti catalysts, respectively. As can be seen from Tables 1-4, Pt and X (X being I, Br, Cl, and F, respectively) form a Pt-X coordination structure.

[0096] Table 1. EDS elemental content of Pt-I / Ti catalysts

[0097]

[0098] Table 2. EDS elemental content of Pt-Br / Ti catalysts

[0099]

[0100] Table 3. EDS elemental content of Pt-Cl / Ti catalysts

[0101]

[0102] Table 4. EDS elemental content of Pt-F / Ti catalysts

[0103]

[0104]

[0105] Example 2

[0106] This embodiment provides a method for preparing a Pt-I / Ti catalyst, including the following steps:

[0107] 1. Prepare the electroplating solution

[0108] Dissolve 0.0006 mol chloroplatinic acid, 0.2 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0109] 2. Pre-treatment of titanium mesh

[0110] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0111] 3. Electroplating deposition of Pt-I metal layer.

[0112] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 20 minutes at a voltage of -0.3V and a stirring speed of 300r to obtain the corresponding Pt-I / Ti catalyst.

[0113] Example 3

[0114] This embodiment provides a method for preparing a Pt-I / Ti catalyst, including the following steps:

[0115] 1. Prepare the electroplating solution

[0116] Dissolve 0.0003 mol chloroplatinic acid, 0.3 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0117] 2. Pre-treatment of titanium mesh

[0118] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0119] 3. Electroplating deposition of Pt-I metal layer.

[0120] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 20 minutes at a voltage of -0.3V and a stirring speed of 300r to obtain the corresponding Pt-I / Ti catalyst.

[0121] Example 4

[0122] This embodiment provides a method for preparing a Pt-I / Ti catalyst, including the following steps:

[0123] 1. Prepare the electroplating solution

[0124] Dissolve 0.0003 mol chloroplatinic acid, 0.4 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0125] 2. Pre-treatment of titanium mesh

[0126] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0127] 3. Electroplating deposition of Pt-I metal layer.

[0128] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 20 minutes at a voltage of -0.3V and a stirring speed of 300r to obtain the corresponding Pt-I / Ti catalyst.

[0129] Example 5

[0130] This embodiment provides a method for preparing a Pt-I / Ti catalyst, including the following steps:

[0131] 1. Prepare the electroplating solution

[0132] Dissolve 0.0003 mol chloroplatinic acid, 0.3 mol NaI, and 0.01 mol potassium nitrate in 200 mL of deionized water.

[0133] 2. Pre-treatment of titanium mesh

[0134] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0135] 3. Electroplating deposition of Pt-I metal layer.

[0136] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 20 minutes at a voltage of -0.3V and a stirring speed of 300r to obtain the corresponding Pt-I / Ti catalyst.

[0137] Example 6

[0138] This embodiment provides a method for preparing a Pt-I / Ti catalyst, including the following steps:

[0139] 1. Prepare the electroplating solution

[0140] Dissolve 0.0003 mol chloroplatinic acid, 0.3 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0141] 2. Pre-treatment of titanium mesh

[0142] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0143] 3. Electroplating deposition of Pt-I metal layer.

[0144] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 20 minutes at a voltage of -0.35V and a stirring speed of 300r to obtain the corresponding Pt-I / Ti catalyst.

[0145] Example 7

[0146] This embodiment provides a method for preparing a Pt-I / Ti catalyst, including the following steps:

[0147] 1. Prepare the electroplating solution

[0148] Dissolve 0.0003 mol chloroplatinic acid, 0.3 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0149] 2. Pre-treatment of titanium mesh

[0150] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0151] 3. Electroplating deposition of Pt-I metal layer.

[0152] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 20 minutes under the conditions of -0.3V voltage and stirring at 350r to obtain the corresponding Pt-I / Ti catalyst.

[0153] Example 8

[0154] This embodiment provides a method for preparing a Pt-I / Ti catalyst, including the following steps:

[0155] 1. Prepare the electroplating solution

[0156] Dissolve 0.0003 mol chloroplatinic acid, 0.3 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0157] 2. Pre-treatment of titanium mesh

[0158] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0159] 3. Electroplating deposition of Pt-I metal layer.

[0160] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 10 min at a voltage of -0.3V and a stirring speed of 300r to obtain the corresponding Pt-I / Ti catalyst.

[0161] The catalyst structures obtained in Examples 2-8 are the same as those in Example 1, and will not be described again here.

[0162] Example 9

[0163] This embodiment provides a method for preparing a Pt-I / Ti catalyst, including the following steps:

[0164] 1. Prepare the electroplating solution

[0165] Dissolve 0.0006 mol chloroplatinic acid, 0.4 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0166] 2. Pre-treatment of titanium mesh

[0167] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0168] 3. Electroplating deposition of Pt-X metal layer.

[0169] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 20 minutes at a voltage of -0.3V and a stirring speed of 300r to obtain the corresponding Pt-X / Ti catalyst.

[0170] Example 10

[0171] This embodiment provides a method for preparing a Pt-X / Ti catalyst, including the following steps:

[0172] 1. Prepare the electroplating solution

[0173] Dissolve 0.0006 mol chloroplatinic acid, 0.2 mol NaI, and 0.01 mol potassium nitrate in 200 mL of deionized water.

[0174] 2. Pre-treatment of titanium mesh

[0175] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0176] 3. Electroplating deposition of Pt-X metal layer.

[0177] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 20 minutes at a voltage of -0.3V and a stirring speed of 300r to obtain the corresponding Pt-X / Ti catalyst.

[0178] Example 11

[0179] This embodiment provides a method for preparing a Pt-X / Ti catalyst, including the following steps:

[0180] 1. Prepare the electroplating solution

[0181] Dissolve 0.0006 mol chloroplatinic acid, 0.2 mol NaI, and 0.01 mol potassium nitrate in 200 mL of deionized water.

[0182] 2. Pre-treatment of titanium mesh

[0183] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0184] 3. Electroplating deposition of Pt-X metal layer.

[0185] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 20 minutes at a voltage of -0.35V and a stirring speed of 300r to obtain the corresponding Pt-X / Ti catalyst.

[0186] Example 12

[0187] This embodiment provides a method for preparing a Pt-X / Ti catalyst, including the following steps:

[0188] 1. Prepare the electroplating solution

[0189] Dissolve 0.0003 mol chloroplatinic acid, 0.2 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0190] 2. Pre-treatment of titanium mesh

[0191] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0192] 3. Electroplating deposition of Pt-X metal layer.

[0193] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 20 minutes under the conditions of -0.35V voltage and stirring at 350r to obtain the corresponding Pt-X / Ti catalyst.

[0194] Example 13

[0195] This embodiment provides a method for preparing a Pt-X / Ti catalyst, including the following steps:

[0196] 1. Prepare the electroplating solution

[0197] Dissolve 0.0006 mol chloroplatinic acid, 0.2 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0198] 2. Pre-treatment of titanium mesh

[0199] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0200] 3. Electroplating deposition of Pt-X metal layer.

[0201] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 10 min at a voltage of -0.3V and a stirring speed of 300r to obtain the corresponding Pt-X / Ti catalyst.

[0202] Example 14

[0203] This embodiment provides a method for preparing a Pt-X / Ti catalyst, including the following steps:

[0204] 1. Prepare the electroplating solution

[0205] Dissolve 0.0003 mol chloroplatinic acid, 0.4 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0206] 2. Pre-treatment of titanium mesh

[0207] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0208] 3. Electroplating deposition of Pt-X metal layer.

[0209] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 10 min at a voltage of -0.3V and a stirring speed of 300r to obtain the corresponding Pt-X / Ti catalyst.

[0210] Example 15

[0211] This embodiment provides a method for preparing a Pt-X / Ti catalyst, including the following steps:

[0212] 1. Prepare the electroplating solution

[0213] Dissolve 0.0006 mol chloroplatinic acid, 0.2 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0214] 2. Pre-treatment of titanium mesh

[0215] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0216] 3. Electroplating deposition of Pt-X metal layer.

[0217] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 20 minutes under the conditions of -0.3V voltage and stirring at 350r to obtain the corresponding Pt-X / Ti catalyst.

[0218] Example 16

[0219] This embodiment provides a method for preparing a Pt-X / Ti catalyst, including the following steps:

[0220] 1. Prepare the electroplating solution

[0221] Dissolve 0.0003 mol chloroplatinic acid, 0.2 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0222] 2. Pre-treatment of titanium mesh

[0223] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0224] 3. Electroplating deposition of Pt-X metal layer.

[0225] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 10 min at a voltage of -0.35V and a stirring speed of 300r to obtain the corresponding Pt-X / Ti catalyst.

[0226] Example 17

[0227] This embodiment provides a method for preparing a Pt-X / Ti catalyst, including the following steps:

[0228] 1. Prepare the electroplating solution

[0229] Dissolve 0.0003 mol chloroplatinic acid, 0.4 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0230] 2. Pre-treatment of titanium mesh

[0231] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0232] 3. Electroplating deposition of Pt-X metal layer.

[0233] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 20 minutes at a voltage of -0.35V and a stirring speed of 300r to obtain the corresponding Pt-X / Ti catalyst.

[0234] Example 18

[0235] This embodiment provides a method for preparing a Pt-X / Ti catalyst, including the following steps:

[0236] 1. Prepare the electroplating solution

[0237] Dissolve 0.0003 mol chloroplatinic acid, 0.4 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0238] 2. Pre-treatment of titanium mesh

[0239] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0240] 3. Electroplating deposition of Pt-X metal layer.

[0241] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 20 minutes under the conditions of -0.3V voltage and stirring at 350r to obtain the corresponding Pt-X / Ti catalyst.

[0242] Example 19

[0243] This embodiment provides a method for preparing a Pt-X / Ti catalyst, including the following steps:

[0244] 1. Prepare the electroplating solution

[0245] Dissolve 0.0003 mol chloroplatinic acid, 0.3 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0246] 2. Pre-treatment of titanium mesh

[0247] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0248] 3. Electroplating deposition of Pt-X metal layer.

[0249] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 15 minutes under the conditions of -0.3V voltage and 300r stirring speed to obtain the corresponding Pt-X / Ti catalyst.

[0250] Example 20

[0251] This embodiment provides a method for preparing a Pt-X / Ti catalyst, including the following steps:

[0252] 1. Prepare the electroplating solution

[0253] Dissolve 0.00045 mol chloroplatinic acid, 0.2 mol NaI, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0254] 2. Pre-treatment of titanium mesh

[0255] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0256] 3. Electroplating deposition of Pt-X metal layer.

[0257] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 15 minutes under the conditions of -0.3V voltage and 300r stirring speed to obtain the corresponding Pt-X / Ti catalyst.

[0258] Example 21

[0259] This embodiment provides a method for preparing a Pt-X / Ti catalyst, including the following steps:

[0260] 1. Prepare the electroplating solution

[0261] Dissolve 0.0015 mol chloroplatinic acid, 0.2 mol NaF, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0262] 2. Pre-treatment of titanium mesh

[0263] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0264] 3. Electroplating deposition of Pt-X metal layer.

[0265] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 15 minutes at a voltage of -0.3V and a stirring speed of 300r to obtain the corresponding Pt-F / Ti catalyst.

[0266] See Figure 25 The figure shows the current density and electrode potential of the Pt-F / Ti catalyst hydrolyzed in natural seawater in this embodiment. Figure 25 The graph shows the catalytic stability of the Pt-F / Ti catalyst after 1 hour of reaction.

[0267] Comparative Example 1

[0268] This comparative example provides a Pt-Ti catalyst, and the specific preparation steps include:

[0269] 1. Prepare the electroplating solution

[0270] Dissolve 0.0003 mol chloroplatinic acid and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0271] 2. Pre-treatment of titanium mesh

[0272] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0273] 3. Electroplating to deposit a Pt metal layer.

[0274] The cleaned titanium mesh was immersed in the above electroplating solution, with the titanium mesh as the cathode and the graphite electrode as the anode. Electrodeposition was carried out for 10 min at a voltage of -0.3V and a stirring speed of 300r to obtain the corresponding Pt-Cl / Ti catalyst.

[0275] 4. Lighting treatment

[0276] The obtained Pt-Cl / Ti catalyst was impregnated in water at 3.75 mW / cm². 2 The Pt-OH / Ti catalyst was obtained by irradiation at a light intensity of 30 min.

[0277] 4. High-temperature calcination

[0278] The obtained Pt-OH / Ti catalyst was placed in a tube furnace and calcined at 200℃ for 4 hours to obtain the Pt-Ti catalyst.

[0279] Figure 5 EDS elemental content table of Pt / Ti catalysts

[0280]

[0281] Comparing Tables 1-5, the EDS distribution diagrams and content tables of the Pt-X / Ti catalyst and Pt / Ti catalyst in Example 1 and Comparative Example 1, it can be seen that there are no halogen coordination atoms in the Pt / Ti catalyst of this comparative example.

[0282] See Figure 14 The figure shows the current density and electrode potential of the Pt / Ti catalyst in this comparative example during electrolysis in seawater (seawater pH = 7.71). Figure 15 The graph shows the stability of the Pt / Ti catalyst after 1 hour of reaction. Compared with Example 1, the catalytic performance shows a more obvious downward trend.

[0283] Comparative Example 2

[0284] This comparative example provides a method for preparing a Pt-F / Ti catalyst, comprising the following steps:

[0285] 1. Prepare the electroplating solution

[0286] Dissolve 0.006 mol chloroplatinic acid, 0.2 mol NaF, and 0.02 mol potassium nitrate in 200 mL of deionized water.

[0287] 2. Pre-treatment of titanium mesh

[0288] The titanium mesh was sequentially immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium substrate was immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0289] 3. Electroplating deposition of Pt-X metal layer.

[0290] The cleaned titanium mesh was immersed in the above electroplating solution, and electrodeposited for 15 min under the conditions of -0.3V voltage and 300r stirring speed to obtain the corresponding Pt-F / Ti catalyst.

[0291] Comparative Example 3

[0292] This comparative example provides a method for preparing a Pt-X / Ti catalyst, including the following steps:

[0293] 1. Prepare the electroplating solution

[0294] Dissolve 0.0003 mol chloroplatinic acid, 0.2 mol HCl and 0.02 mol potassium nitrate in 200 mL of deionized water to form an electroplating solution.

[0295] 2. Pre-treatment of titanium mesh

[0296] The titanium mesh was successively immersed in anhydrous ethanol and anhydrous acetone and sonicated for 5 minutes each to remove surface oil. The titanium mesh was then immersed in 0.5 mol / L sulfuric acid solution and sonicated for 5 minutes to remove surface oxides.

[0297] 3. Electroplating deposition of Pt-X metal layer.

[0298] The cleaned titanium mesh was immersed in the above electroplating solution, and electrodeposited for 20 min under the conditions of -0.3V voltage and 300r stirring speed to obtain the corresponding Pt-X / Ti catalyst.

[0299] Stability performance test:

[0300] Under normal temperature and pressure conditions, the Pt-F / Ti, Pt-Cl / Ti, Pt-Br / Ti, Pt-I / Ti catalysts prepared in Example 1, as well as the Pt-Ti catalyst prepared in Comparative Example 1, were respectively placed in natural neutral seawater (seawater pH = 7.71) for electrolysis. The reaction results are shown in [reference needed]. Figure 6 (Pt-I / Ti) Figure 8 (Pt-Br / Ti) Figure 10 (Pt-Cl / Ti) Figure 12 (Pt-F / Ti) Figure 14 (Pt-Ti) is a stability graph of each catalyst after 1 hour of reaction. It can be seen that the Pt-X / Ti catalyst has better stability than the Pt-Ti catalyst, indicating that the coordination of halogen atoms can increase the stability of the Pt / Ti catalyst. According to the graph, the stability ranking is: Pt-I / Ti catalyst > Pt-Br / Ti catalyst > Pt-Cl / Ti catalyst > Pt-F / Ti.

[0301] Table 6 Catalytic performance of Examples 9-20

[0302]

[0303] Furthermore, referring to Table 6, the table shows the current density and voltage rise after 30 minutes of electrolysis of the Pt-X / Ti catalysts prepared in Examples 9-20 and the Pt-Ti catalyst prepared in Comparative Example 2 in seawater (pH = 7.71). Figure 7 , Figure 9 , Figure 11 , Figure 13 and Figure 15 The current density and electrode potential graphs for the Pt-F / Ti, Pt-Cl / Ti, Pt-Br / Ti, and Pt-I / Ti catalysts prepared in Example 1 and the Pt-Ti catalyst prepared in Comparative Example 1, respectively, were obtained by electrolysis in seawater (pH = 7.71). It can be seen that the performance of the coordinated Pt-X / Ti electrode is better than that of the uncoordinated Pt / Ti electrode, and the HER performance ranking of the catalysts is Pt-F / Ti > Pt-Cl / Ti > Pt-Br / Ti > Pt-I / Ti. The Pt-X / Ti catalysts prepared in Examples 1-8, when placed in seawater (pH = 7.71), exhibited electrochemical performance and stability similar to those in Example 9, with a current density of -0.45 to -0.5 V and a voltage increase of 30 to 75 mV after 30 minutes of operation. This indicates that the technical solution of this invention can obtain a catalyst material with stable electrocatalytic performance and effectively avoid the problem of easy scaling at the cathode during seawater electrolysis. Further details are omitted here.

[0304] In summary, by employing an in-situ synthesis coordination method, a modified metal layer is deposited on the surface of a first metal substrate to form a composite metal material. The modified metal layer comprises a second metal bonded to coordinating atoms via coordinate bonds and deposited on the surface of the first metal substrate. Using this invention, the in-situ synthesis coordination method allows the second metal to replace and deposit on the surface of the first metal substrate material, bonding with halogen atom ligands and depositing on the surface of the first metal substrate material, rather than penetrating into the interior of the first metal substrate. This effectively improves catalyst activity, effectively inhibits scaling on the catalyst surface, and improves catalyst stability.

[0305] It should be noted that the above description is only a preferred embodiment of the present invention and the foregoing embodiments have been used to describe the present invention in detail. The embodiments are not intended to limit the present application. Although those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features, any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included within the protection scope of the present invention.

Claims

1. A method for preparing a binary metal catalyst material containing a coordination structure, characterized in that, A modified metal layer is deposited on the surface of a first metal substrate using an in-situ synthesis coordination method to form a composite binary metal material; wherein... The modified metal layer comprises a second metal and coordinating atoms bonded together to form a ligand structure, which is deposited on the surface of the first metal substrate.

2. The method for preparing the binary metal catalyst material according to claim 1, characterized in that, The in-situ synthesis coordination method includes: immersing a first metal substrate in an electroplating or chemical plating solution using an electroplating or chemical plating process, and then depositing the second metal particles together with the coordinating atoms on the surface of the first metal substrate through coordination bonds.

3. The method for preparing the binary metal catalyst material according to claim 2, characterized in that, The first metal matrix includes either a titanium matrix or a nickel matrix; The purity of the first metal matrix is ​​≥99%; And / or, the second metal includes at least one of palladium, platinum, ruthenium, and manganese; And / or, the second metal source is at least one of the sulfate, nitrate, and chloride salts of the second metal; And / or, the coordinating atom is a halogen atom.

4. The method for preparing the binary metal catalyst material according to claim 1, characterized in that, The titanium matrix includes at least one of titanium sheet, titanium mesh, and titanium foam. And / or, the nickel matrix includes at least one of nickel sheet, nickel mesh, and nickel foam.

5. The method for preparing the binary metal catalyst material according to claim 2, characterized in that, The electroplating solution or the chemical plating solution is a mixed solution comprising at least the second metal source solution, the coordination ion solution, and the salt solution; And / or, the conditions of the electroplating process include: a temperature of 20 to 50°C, a voltage of -0.1 to 1.5V, a time of 5 to 30 minutes, and the concentration of the metal source in the electroplating solution being 0.0015 to 0.015 mol / L and the concentration of the salt solution being 0.05 to 0.2 mol / L; And / or, the conditions of the electroless plating process include: the electroless plating solution contains 0.01-1 mol / L of a second metal source, 0.01-1 mol / L of a complexing agent and 0.01-1 mol / L of a reducing agent, and the electroless plating time is 5-30 min.

6. The method for preparing the binary metal catalyst material according to claim 5, characterized in that, The salt solution includes at least one of potassium nitrate, potassium acetate, and potassium sulfate; And / or, the complexing agent includes at least one of sodium tartrate, sodium citrate, ethylenediaminetetraacetic acid, and sodium pyrophosphate; And / or, the reducing agent includes at least one of sodium hypophosphite, sodium borohydride, and borane.

7. The method for preparing the binary metal catalyst material according to any one of claims 1-6, characterized in that, The first metal matrix material also includes pretreatment before deposition; The pretreatment includes: removing contaminants from the surface of the metal substrate using at least an organic solvent and / or an alkaline solution; and removing the oxide layer from the surface of the metal substrate using at least an acidic reagent.

8. A binary metal catalyst material, prepared by the method for preparing binary metal catalyst materials as described in any one of claims 1-7.

9. The binary metal catalyst material according to claim 8, characterized in that, The content of the second metal atoms deposited on the surface of the first metal substrate is 70-75 at%, and the content of ligand atoms is 25-30 at%.

10. The binary metal catalyst material according to claim 8, characterized in that, The second metal is platinum, the ligand atoms are halogen atoms, and the first metal is titanium.

11. The use of a binary metal catalyst material as described in any one of claims 8-10 in the electrolysis of neutral seawater to produce hydrogen.

12. An electrode for producing hydrogen by electrolysis of neutral seawater, characterized in that: The electrode comprises the binary metal catalyst material according to any one of claims 8-10.

13. A water electrolysis hydrogen production system, comprising a hydrogen evolution electrode and an oxygen evolution electrode, characterized in that: At least one of the hydrogen evolution electrode and the oxygen evolution electrode comprises the binary metal catalyst material according to any one of claims 8-10; or the electrode for producing hydrogen by electrolysis of neutral seawater according to claim 12.

Citation Information

Patent Citations

  • Method for improving surface energy of nickel metal, nickel-copper binary metal material and application of nickel-copper binary metal material

    CN118222953A